An experimental study on the potential purchase behavior of Chinese consumers of new energy hybrid electric vehicles - Guo, Qing; Liu, Youqian; Cai, Luxin (Frontiers in Environmental Science, 2023)
For the automotive industry, the bright future of new energy vehicles has received great attention, and the new energy hybrid electric vehicles under its classification are gradually entering the public vision. By using the methods of questionnaire survey and scene experiment, based on the data of 379 questionnaires from 24 cities across the country and the results of scene experiment, and by using SPSS software, the "purchase preference for new-energy hybrid electric vehicles" of different types of consumers in our country and its influential factors are experimentally studied. The findings are as follows: (1) Different categories of consumers have a large gap in their cognitive preferences for new energy hybrid electric vehicles; (2) There is not much difference in "purchase preference for new energy hybrid electric vehicles" among different categories of consumers; (3) The improvement of education and income has a significant effect on promoting the "environmental awareness" of consumers; (4) Consumers' perception of the government's new energy vehicle policy does not significantly affect their purchase preference for new energy hybrid electric vehicles. Based on the above conclusions, this paper puts forward policy recommendations aimed at promoting new energy hybrid electric vehicles.